A novel approach for dynamic traffic lights management based on Wireless Sensor Networks and multiple fuzzy logic controllers. Issue 13 (1st August 2015) - Collotta, Mario; Lo Bello, Lucia; Pau, Giovanni
<x xml:space="preserve">Abstract</x> Highlights Flexible, scalable traffic lights dynamic control system for isolated intersections. Multiple parallel fuzzy controllers dynamically manage both the phase and green time. Outperforms other works in terms of vehicle waiting time and balancing between phases. Very effective under heavy traffic and when phases have unbalanced arrival rates. Lightweight effective implementable on COTS devices: broad practical impact expected.